Percepção ambiental na conservação do patrimônio escolar nas escolas públicas de Pojuca – Bahia - Viana, Lenice dos Santos (2018)
This paper aims to analyze the environmental perception of students from public schools in the city of pojuca- bahia, addressing their relevance to the conservation of the school environment and the implications of lack of conservation for society as a whole.The study points out students’ suggestions for the problem of school space degradation. It also investigates whether actions are developed by the school regarding environmental education that stimulate and educate its students to engage in the preservation of the environment. To begin, the concepts of education and environmental perception are presented, as well as Brazilian laws and instruments dealing with the theme. The study is an interpretive and qualitative one, carried out from the application of questionnaires in classes of elementary and secondary education of public schools in Pojuca- Bahia. The results point to the need for continuous actions in the school that alert students to a better knowledge about the environment, important for awareness and preservation of the spaces in which they live. Although they recognize the school space as an integral part of the environment, it was noted that most of the students associate it to a greater degree to the natural environment (vegetation, man, rivers). Moreover, although many students claim to have witnessed degradation actions in the school environment, they have become collaborators in the conservation of the environment. And they attribute the fact of recidivist students the violent acts to the patrimony to the lack of severe punishments.Students recognize that non-conservation of school assets can make the environment unpleasant, compromise learning, and even destroy the school, a fact that harms students and the community. Adoption of sustainable school practices and school based awareness raising activities is necessary to make everyone (officials, public authorities and the community at large) aware of their duty to collaborate in a balanced environment, whose objections can lead to tragic school and for all society.